Competition in Indian Banking. (IMF Working Papers; Working Paper ;, 2005)
It is widely perceived that competition in the Indian banking sector has increased since the inception of the financial sector reforms in 1992. Using annual data on scheduled commercial banks for the period 1996-2004, the paper evaluates the validity of this claim in the Indian context. The empirical evidence reveals that the Indian banking system operates under competitive conditions and earns revenues as if under monopolistic competition.